ANALISIS PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR - Febby Rahma Putri; Yantoro; Desy Rosmalinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the planning, implementation, and evaluation processes of differentiated instruction in the IPAS subject for Grade V elementary students. The problem arises from teachers’ difficulties in accommodating students’ diverse learning styles, interests, and readiness within the Merdeka Curriculum framework. This research used a descriptive qualitative approach with data collected through observation, interviews, and documentation. The subjects were a Grade V teacher and students at SDN 198/I Pasar Baru. The findings show that the teacher applied differentiation through three main components: content, process, and product. Diagnostic assessments were conducted to identify students’ readiness, followed by the design of learning activities adapted to their learning styles (visual, auditory, kinesthetic). Instruction was carried out in groups according to student ability levels, and evaluation was conducted using formative assessment and class reflection. Differentiated instruction was shown to enhance student engagement, self-confidence, and conceptual understanding. However, challenges such as limited time and the complexity of preparing differentiated materials remain. This study recommends ongoing training and support for teachers to effectively design and manage student-centered, adaptive learning environments.